A man with opaque left hemithorax due to hemorrhagic exudate - santos, Vitorino Modesto; santos, Lister Arruda Modesto (Revista de Medicina e Saúde de Brasília, 2019)
The authors briefly present a case study of opaque hemithorax due to voluminous hemorrhagic pleural effusion, and comment data of studies about malignant pleural effusions. This very ominous condition may be associated with diagnostic challenges, and must be treated as earliest as possible, to propitiate better quality of life to the affected patients. Authors emphasize the role of imaging studies to guide the pleural drainages and biopsies. The major primary and secondary causes of malignant pleural effusions are also commented.